Development of video-assisted work and energy learning tools by blended-flipped classroom model to improve students creative thinking skills - Talitha Gita Andani; Ahmad Harjono; I Wayan Gunada (Jurnal Pijar Mipa, 2022)
This study aims to produce a product in the form of work and energy learning tools by a blended-flipped classroom model. The product is assisted by a feasible, practical, and effective video to improve students' creative thinking skills. The developed products are Lesson Plans, Student Worksheets, learning videos, and creative thinking skills test instruments. The type of research used is research and development using the Dick, Carey, & Carey model. The stages of this research are analysis of needs and objectives, analysis of learning, analysis of students, formulating performance goals, developing instruments, developing learning strategies, developing learning materials, conducting formative evaluations, and revisions. The research subjects were three Physics Education University of Mataram lecturers and a physics teacher at senior high school SMA-IT Abu Hurairah Mataram as validators and 32 students of grade tenth as field trial subjects. The instruments used include validation sheets, observation sheets of learning implementation, student response questionnaires to implement learning, and creative thinking skills tests. The feasibility of learning tools is obtained from expert and practitioner validators' average validity value and percentage of agreement (PA). The device's practicality is obtained from the IJA percentage and positive student response related to the implementation of learning. The effectiveness of learning devices is obtained from the increasing students' pretest and posttest scores, which are analyzed using the N-Gain test. The analysis results show that the instrument is valid, with an average validity score in the very good and reliable category, with a mean PA score of more than 75%. The level of implementation of learning is 100% in the very good criteria, and the student responses showed a positive percentage of 81% in the very practical category. The average result of the N-Gain of students' creative thinking skills is 0.41 in the moderate category. In conclusion, the work and energy learning tools of the blended-flipped classroom model assisted by a video are feasible, practical, and effective in improving students' creative thinking skills.